THE INDIVIDUALISM/COLLECTIVISM DICHOTOMY IN N. HAWTHORNE’S NOVEL “THE SCARLET LETTER”: Received: 30th May 2022; Revised: 13th June 2022, 29th June 2022; Accepted: 30th June 2022 - Madani, Shpëtim (PEOPLE: International Journal of Social Sciences, 2022)
This paper seeks to examine the novel The Scarlet Letter, published in 1850, by Nathaniel Hawthorne through individualism/collectivism dichotomy, highlighting the major chasm between the harsh 17th-century puritan community that demands total conformity from its members and heroine’s incessant struggle for individualism. Based on qualitative research, the analysis starts with a short introduction of individualism/collectivism dichotomy. It subsequently highlights the intense clash arising from the puritan morality and the heroine’s determination to create her own moral rules. The study found out that Hester’s strength of character and support for the community help to abate the dichotomy between the two parties, which leads to a fair degree of mutual acceptance.